Quality of Life in Patients With Breast Cancer: A Pilot Study - Vida Karalienė; Zita Petravičienė; Lina Budrienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Breast cancer is the most common oncological disease among women worldwide, significantly affecting patients’ physical, emotional, and social well-being. Although treatment methods have advanced, they often cause side effects that negatively impact quality of life.